2019
DOI: 10.1667/rr15193.1
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic Receptor Signaling Regulates the Response of Tumors to Ionizing Radiation

Abstract: While ionizing radiation is a major form of cancer therapy, radioresistance remains a therapeutic obstacle. We have previously shown that the mandated housing temperature for laboratory mice (~22°C) induces mild, but chronic, cold stress resulting in increased circulating norepinephrine, which binds to, and triggers activation of, beta-adrenergic receptors (β-AR) on tumor and immune cells. This adrenergic signaling increases tumor cell intrinsic resistance to chemotherapy and suppression of the anti-tumor immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…While our work here reveals that adrenergic stress is a major factor dictating the overall response to radiation in vivo, we have also observed that increased β-AR signaling through treatment with the agonist, isoproterenol, can directly increase tumor cell resistance to radiation in vitro 37 . Thus, how stress affects both direct (tumor cell intrinsic) as well as indirect targets (including anti-tumor immunity as demonstrated here), to regulate the overall radiation response in vivo remains to be established.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…While our work here reveals that adrenergic stress is a major factor dictating the overall response to radiation in vivo, we have also observed that increased β-AR signaling through treatment with the agonist, isoproterenol, can directly increase tumor cell resistance to radiation in vitro 37 . Thus, how stress affects both direct (tumor cell intrinsic) as well as indirect targets (including anti-tumor immunity as demonstrated here), to regulate the overall radiation response in vivo remains to be established.…”
Section: Discussionmentioning
confidence: 53%
“…We, and others, have also shown that adrenergic signaling directly increases tumor cell resistance to killing by chemotherapy and targeted therapies 22,35,36 , and our lab recently showed that standard housing temperature-induced adrenergic stress signaling increases intrinsic tumor cell resistance and constrains the antitumor efficacy of ionizing radiation 37 . However, neither we nor others have ever explored the relationship between the frequency of abscopal effects and housing temperature, or the role of host adrenergic stress signaling in general on anti-tumor immunity following RT.…”
mentioning
confidence: 88%
“…TN may have a positive influence on various cancer therapies. Mice with colon adenocarcinoma had lower responses to irradiation and chemotherapy at ST compared to TT (56). Mice bearing pancreatic tumors had higher sensitivity to cytotoxic treatments at TT compared to ST (25).…”
Section: Cancermentioning
confidence: 94%
“…This response was attributed to an enhanced cytotoxic-cell mediated immune response characterized by increases in populations of natural killer cells; natural killer T cells; gdT cells; CD8+ T cells; and, IFN-g at the higher temperatures (57). In addition, resistance to treatments at ST was mostly attributed to elevated levels of NE because treatment with beta-blockers resulted in responses similar to those observed at TT (4,25,56,58,59,76). Interestingly, higher levels of anti-apoptotic molecules (BAD, MCL-1, BCL-2, and BCLxL) and CREB, a transcription factor involved in the survival of these molecules were seen at ST compared to TT, which may also contributed to lower treatment efficacy at ST (25).…”
Section: Cancermentioning
confidence: 99%
“…They linked this effect to increased stress-induced β2-AR stimulation in CD8 + T-cells. A recent study [ 81 ] demonstrated that stressed tumor bearing mice had a poorer response to radiation; conversely, an improved anti-tumor response, and increased numbers of CD8 + and CD4 + T-cells expressing IFNγ and GzmB in irradiated tumors were found in the tumors of mice treated with propranolol, suggesting that β-AR signaling on lymphocytes might be involved in hampered immunity by irradiation. Altogether, the aforementioned studies reveal important mechanisms by which stress can block immune responses following radiation.…”
Section: Modulation Of the Tumor Microenvironment By Chronic Stresmentioning
confidence: 99%